Keteladanan Ibu dalam Al-Qur’an; Analisis terhadap Penafsiran ibn Katsir - Wira Elmuhriani; Syafruddin Syafruddin; Widia Fithri; Edriagus Saputra (Hikmah, 2022)
This study aims to reveal the example of a mother in the Qur'an, with a focus on the analysis of the interpretation of Imam Ibn Katsir. The selection of this interpretation is based on the unique style of the tahlili interpretation, which contains stories from which ibrah can be exemplified. This problem is examined using the Library Research method using a thematic interpretation approach, and then the author examines the literature related to the study of the excellent story of Mother in the Qur'an. Based on the research that has been done, it can be concluded that there are three good stories of mothers in the Qur'an, namely Ayarikha, the mother of Prophet Musa a.s. which is contained in the letter al-Qasas: 7 and Surat al-Baqarah: 233, Siti Hajar, the mother of the Prophet Ismail a.s. which is found in sura al-Baqarah: 158 and in sura Ibrahim: 37, while Hannah Ibu Maryam is found in sura Ali Imran: 35-37. While the exemplary values ​​are given by mothers in the Qur'an from the perspective of Ibn Katsir's interpretation, such as conceiving, giving birth, breastfeeding, caring for, looking after and nurturing their children and also providing exemplary education that can provide compassion. Apart from that, a mother also has to set an example in obedience to Allah, trust and never give up, be patient, pray and make vows, and give a good name and an excellent place to live.